Social Norms and Information in Menstrual Health Management - Silvia Castro; Kristina Czura (ZBW - Leibniz Information Centre for Economics, 2021)
Inadequate hygiene during menstruation can have severe consequences, such as adverse health effects, lower educational attainment and higher work absenteeism. Cultural taboos and social norms surrounding menstruation may be responsible for misinformation on menstrual hygiene and may also prevent attempts to improve knowledge. Using lab-in-the-field experiments with women in rural Bangladesh, we measure social norms in the form of empirical and normative expectations on menstrual health and hygiene explicitly and relate them to behavior and knowledge. We provide an information intervention on menstrual health and hygiene and observe how this changes the perceived social norms. We find that the majority of women report decreased physical and mental well-being, in particular stress and shame, during their menstruation. Further, we find knowledge gaps on the proper use of hygienic material for menstrual health management and that reported adverse health behavior is well reflected in empirical and normative expectations. The information intervention helps to correct harmful social norms, although results are more pronounced for women who have more autonomy and agency over their own decisions.
Keywords: I12; I15; D91; O12; 330; Social norms; menstrual health management; menstrual hygiene; information; adverse health behavior